Restructuring a higher education institution: A case study from a developing country - Sohail M.S.; Daud S.; Rajadurai J. (2023)
Purpose - The competitive environment facing all organizations has forced many of them to choose strategies that enhance organizational effectiveness and efficiency. Re-engineering is one of the tools used in administering productivity improvements, cost control and asset management. Design/methodology/approach - This paper examines the re-engineering process of a higher education institution (HEI) in Malaysia. The impact of cost reduction strategies linked to the overall performance of the organization is discussed in comparison to management system prior to restructuring; vision, mission and strategic direction; core business processes; financial performance analysis; corporate and organizational structure; reorganization of learning centers; courses offered; human resource policies and customers feedback. Findings - The study found that generally the HEI focused on the cost-cutting strategy especially on cost of sales and operational expenses. Consequently, there were increases in the utilization of the learning; occupancy of the learning centers; number of home courses offered increased and a decrease in employment of part-time teaching staff. There were also marked improvements in academic networks and partnerships that provide for knowledge exchange and transfer. Originality/value - Although a number of studies have been carried out in Malaysia, very few have concentrated on restructuring process of higher educational institutions. This study critically examines the restructuring process and the major gains of a higher educational institution that embarked on a restructuring program to fully meet its objectives of high quality education and training. Emerald Group Publishing Limited.